A novel, non-neuronal acetylcholinesterase of schistosome parasites is essential for definitive host infection - Skelly, Patrick J.; Da’dara, Akram A. (Frontiers in Immunology, 2023)
Schistosomes are long-lived parasitic worms that infect >200 million people globally. The intravascular life stages are known to display acetylcholinesterase (AChE) activity internally as well as, somewhat surprisingly, on external tegumental membranes. Originally it was hypothesized that a single gene (SmAChE1 in Schistosoma mansoni) encoded both forms of the enzyme. Here, we demonstrate that a second gene, designated “S. mansoni tegumental acetylcholinesterase, SmTAChE”, is responsible for surface, non-neuronal AChE activity. The SmTAChE protein is GPI-anchored and contains all essential amino acids necessary for function. AChE surface activity is significantly diminished following SmTAChE gene suppression using RNAi, but not following SmAChE1 gene suppression. Suppressing SmTAChE significantly impairs the ability of parasites to establish infection in mice, showing that SmTAChE performs an essential function for the worms in vivo. Living S. haematobium and S. japonicum parasites also display strong surface AChE activity, and we have cloned SmTAChE homologs from these two species. This work helps to clarify longstanding confusion regarding schistosome AChEs and paves the way for novel therapeutics for schistosomiasis.